The impacts of early childhood investment: an approach through latent cognitive skills - Pires, Luciana Neves (2018)
This work contributes to the literature of human capital formation by estimating the impact of early childhood investment (by means of preschool attendance) over cognitive skill development. Using a longitudinal panel dataset for a single municipality, we draw the distribution of latent cognitive and non-cognitive factors and consider a dynamic model of skill formation. We find our Constant Elasticity Substitution (CES) production function to be a Cobb-Douglas. The complementarity and share parameters of the CES are stable in diverse specifications tested. We find that early investment matters for cognitive skill accumulation during childhood. Preliminar estimation for long-term cognitive production presents evidence of self-productivity (skill begets skill). Since cognitive skill is persistent overtime, early childhood investment has a positive cumulative impact in the long-term by boosting cognitive skills in earlier stages.